Using Magnetoencephalography to Elucidate the Principles of Deep Brain Stimulation - Kringelbach, M; Hansen, P; Green, A; Aziz, T (Oxford University Press, 2010)
Deep brain stimulation (DBS) is a powerful clinical tool that has provided remarkable therapeutic benefits for otherwise treatment-resistant movement and affective disorders. The precise mechanisms of action for DBS remain uncertain but are likely to result through causal manipulation of both local and distributed brain networks. Recently, noninvasive neuroimaging methods such as magnetoencephalography have started to be used in conjunction with DBS in order to map the fundamental mechanisms of normal and abnormal oscillatory synchronization underlying human brain function. This chapter begins with an introductory overview of the current state-of-art of DBS and the previous use of neuroimaging techniques with DBS. It then describes the methods and results of using MEG to measure both low and high frequency stimulation. It discusses the importance of the findings, as well as potential confounds and future possibilities of combining MEG and DBS.